McGraw-Hill's dictionary of American slang and colloquial expressions (McGraw-Hill, 2023)
This new edition of McGraw-Hill's Dictionary of American Slang and Colloquial Expressions offers complete definitions of more than 12,000 slang and informal expressions from various sources, ranging from golden oldies such as . . . golden oldie, to recent coinages like shizzle (gangsta), jonx (Wall Street), and ping (the Internet). Each entry is followed by examples illustrating how an expression is used in everyday conversation and, where necessary, International Phonetic Alphabet pronunciations are given, as well as cautionary notes for crude, inflammatory, or taboo expressions This edition also features a fascinating introduction on "What is Slang?," a Thematic Index that cross-references expressions by standard terms--such as Angry, Drunk, Food, Good-bye, Mess-up, Money, and Stupidity -- and a Hidden Word Index that lets you identify and locate even partially remembered expressions and phrases.

Barron's American slang dictionary and thesaurus (Barrons Educational Series, 2009)
Presents English language slang terms and phrases in alphabetical and thematic formats, and provides explanations for slang usage and phrase origins.

Handbook of commonly used American idioms (Barron's, 2013)
Small enough to fit in purse or pocket, this dictionary presents approximately 2,500 American-English idiomatic words and expressions with their meanings. "In one's element" ... "nail down" ... "off base" and most other American idioms are composed of simple words that somehow take on brand-new meanings when they are combined. Here's a handy reference guide to them all for ESL students, foreign travelers in North America, and anybody with an interest in language usage. Expressions are listed alphabetically, identified according to their part of speech, and categorized as formal, informal, slang, or literary. Each expression is defined and supplemented with an illustrative sentence.